Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 4 Quadratic Functions and Factoring - 4.4 Solve ax(squared) + bx + c = 0 by Factoring - 4.4 Exercises - Quiz for Lessons 4-1-4.4 - Page 265: 6



Work Step by Step

We use the FOIL method. Then we simplify until the equation is in the form $y=ax ^2+bx+c$. Hence: $g(x)=5(x+6)^2-2=5(x^2+6x+6x+36)-2=5(x^2+12x+36)-2=5x^2+60x+180-2=5x^2+60x+178$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.